Implementation and challenges of sustainable tourism programs in Bali - Januar, Rizky (Bali Tourism Board, 2024)
The rapid growth of tourism in Bali has led to extensive development of accommodations, infrastructure, and facilities, positioning the island as a major tourist destination. However, this growth has brought significant challenges, including environmental degradation, cultural commodification, and social inequalities. The overexploitation of natural resources, unsustainable waste management, and deforestation have raised concerns about the island’s long-term ecological health. Additionally, the commercialization of cultural traditions and rising land prices have disrupted local communities and eroded the authenticity of Balinese heritage. In response, Indonesia has launched the